Evaluating viral filtration efficiency in non-centralized air-conditioning systems: a novel approach grounded in medical experimental data - Yin Zhang; Ying Zhao; Jin Li; Ying Huang (Geomatics, Natural Hazards & Risk)
This study enhances the understanding of virus removal efficiency by filters, crucial for predicting respiratory disease transmission risk and guiding outbreak prevention. Current research often neglects the survival behaviour of pathogens. Addressing this, our research develops a novel approach anchored in medical experimental data. A mathematical model was established to depict the dynamic changes in particulate concentration within non-centralized air-conditioned rooms, considering indoor and outdoor concentrations, natural ventilation, and filter dynamics. The model’s reliability was affirmed through particle and aerosolized pathogen filtration experiments, showing an R2 value over 0.99, indicating strong agreement with empirical data. Analysis of filter operation, both with and without infection sources during epidemics, reveals that the use of split air conditioners and filters significantly reduces pathogen concentration. Pathogens trapped in filters undergo natural decay, considerably lowering transmission risk compared to airborne states. This research offers a scientifically grounded, precise methodology for evaluating respiratory disease transmission risks, contributing substantially to public health management.